Alpha-particle emission from the deep-inelastic reaction 1354 MeV Ho-165+ Ta-181 - Sobotka, L. G.; Mc Donald, R. J.; Wozniak, G. J.; Morrisey, D. J.; Pacheco, A. J.; Moretto, L. G. (The American Physical Society, 1982)
Fil: Sobotka, L. G. Nuclear Science División, Lawrence Berkeley Laboratory, University o f California; Estados Unidos